Downshifting of highly energetic photons and energy transfer by Mn-doped perovskite CsPbCl3 nanocrystals in hybrid organic/silicon nanostructured solar cells. (November 2020) - Abdelbar, Mostafa F.; El-Kemary, Maged; Fukata, Naoki
Abstract: The downshifting of highly energetic photons in the ultraviolet region has the benefit of extending the spectral response and decreasing the thermalization effect in Si-related solar cells. Herein, we report low-cost hybrid organic/inorganic solar cells with minimized spectral losses with directly-deposited Mn-doped perovskite CsPbCl3 nanocrystals (NCs) on the surface of Si nanotips with PEDOT:PSS acting as the hole transporting and passivating layer. The CsPbCl3 NCs act as highly efficient radiative and non-radiative energy transfer centers. Manganese doping in CsPbCl3 NCs also drastically enhances photoluminescence quantum yields due to the charge transfer of photoinduced excitons from the CsPbCl3 host to the dopant Mn 2+ centers. Finally, the Mn doped CsPbCl3 NCs enhance the cell properties and give a high power conversion efficiency of 13.48%. Graphical abstract: A Novel hybrid organic/inorganic silicon nanotips solar cell employing CsPbCl3 and Mn doped CsPbCl3 perovskite NCs as a downshifting layer exhibits a drastic enhancement in the cell characteristics, which is due to the radiative and nonradiative energy transfer (RET & NRET) from the NCs to underlying silicon nanostructure. Image 1 Highlights: Nanocrystalline Mn doped CsPbCl3 with different Pb: Mn feeding ratio were prepared and show interesting optical characteristics. Silicon nanowire arrays were fabricated by metal catalyzed chemical etching and modified into tapered Nanotips structure with broadband absorption and was used to fabricate high-efficiency hybrid PEDOT:PSS silicon solar cell. The application of NCs on the interface of PEDOT: PSS /silicon nanotips solar cell improved the cell characteristics and enhance the PCE to 13.48% due to radiative and non-radiative energy transfer from the NCs to underlying silicon.